The epidemiology of osteoporosis. Issue 1 (13th April 2020) - Clynes, Michael A; Harvey, Nicholas C; Curtis, Elizabeth M; Fuggle, Nicholas R; Dennison, Elaine M; Cooper, Cyrus
Abstract: Introduction: With a worldwide ageing population, the importance of the prevention and management of osteoporotic fragility fractures is increasing over time. In this review, we discuss in detail the epidemiology of fragility fractures, how this is shaped by pharmacological interventions and how novel screening programmes can reduce the clinical and economic burden of osteoporotic fractures. Sources of data: PubMed and Google Scholar were searched using various combinations of the keywords 'osteoporosis', 'epidemiology', 'fracture', 'screening', `FRAX' and 'SCOOP'. Areas of agreement: The economic burden of osteoporosis-related fracture is significant, costing approximately $17.9 and £4 billion per annum in the USA and UK. Areas of controversy: Risk calculators such as the web-based FRAX® algorithm have enabled assessment of an individual's fracture risk using clinical risk factors, with only partial consideration of bone mineral density (BMD). Growing points: As with all new interventions, we await the results of long-term use of osteoporosis screening algorithms and how these can be refined and incorporated into clinical practice. Areas timely for developing research: Despite advances in osteoporosis screening, a minority of men and women at high fracture risk worldwide receive treatment. The economic and societal burden caused by osteoporosis is a clear motivation for improving the screening and management of osteoporosis worldwide.